Analysis of Social Media and Social Media Crimes - Vinny Sharma; Tushaar Chaturvedi; Abhiramy S. Shenoy (Indian Journal of Forensic Medicine and Pathology, 2025)
The rapid expansion of social media platforms in recent years has completely changed worldwide connectivity and communication. These platforms offer new obstacles in terms of social media crime even as they provide never-beforeseen chances for online communication, community building, and information exchange. This abstract summarizes key subjects, trends, and implications while offering an accessible overview of the connection between criminal activity and social media. The article highlights the advantages of social media, emphasizing how it may help people interact, spread knowledge, and support social activity. Social media platforms function as digital environments where people can express themselves, share personal stories, and assist in the growth of a digital community. However, this portion digs into the multiple drawbacks of social media. In Open-Source Intelligence (OSINT), data collection and pro𿿿lingof readilyavailable private and public sources are undertaken. Resources for sector information for business intelligence and personal data. The internet and other social media sites like Facebook, Gmail, Twitter, and What’s App, Instagram are some examples of these sources. Although there has been much discussion and investigation about the risks, weaknesses, and effects of using social networking sites, the purpose of this study is to reduce bias. Objective: To perform a thorough analysis and summary of the results of recent empirical research on open source and cyber intelligence pro𿿿ling to𿿿nd nline ocial networks’ faults and threats for mitigation targets.